An Assessment of the Corporate Image Building Strategies Adopted at the School of Nursing, Ogoja, Cross River State - Emuru, Linus Ejunka; Aruku, Kalita Joseph; Itam, Barnabas Clement; Ikangkang, Joseph (Darul Yasin Al Sys, 2025)
The study examined the strategies employed by the School of Nursing, Ogoja to enhance their corporate image among its various stakeholders. The main objective was to examine ways in which organisations can promote a more favourable corporate image for themselves. In order to achieve the objective, a structured questionnaire designed in a four-point Likert format was used to gather data, which were analyzed using weighted mean score and presented in frequency tables. The study population comprised students and staff members of the institution, with a sample size of 200 respondents selected through purposive and random sampling methods. The findings revealed that the School of Nursing, Ogoja lacks a well-defined public relations department, leading to ineffective communication channels and overall inadequacy in their corporate image building strategies. It was recommended that the institution should establish a dedicated public relations office to address these challenges and develop more robust and successful strategies for enhancing their corporate image.